3D Macroporous Solids from Chemically Cross‐linked Carbon Nanotubes. Issue 6 (15th October 2014) - Ozden, Sehmus; Narayanan, Tharangattu N.; Tiwary, Chandra S.; Dong, Pei; Hart, Amelia H. C.; Vajtai, Robert; Ajayan, Pulickel M.
<x xml:space="preserve">Abstract</x> Suzuki reaction for covalently interconnected 3D carbon nanotube (CNT) architectures is reported. The synthesis of 3D macroscopic solids made of CNTs covalently connected via Suzuki cross‐coupling, a well‐known carbon–carbon covalent bond forming reaction in organic chemistry, is scalable. The resulting solid has a highly porous, interconnected structure of chemically cross‐linked CNTs. Its use for the removal of oil from contaminated water is demonstrated. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>